An overview of current technological developments in apparel fit customization - Zhenzhen, Huang; Faridah, Sahari (Emerald Publishing Limited, 2025)
Purpose – This study reviews the literature that discusses the technologies that will influence fit customization (FC). The purpose of this study is to clearly understand the current progress of such technology and the potential future development path. Design/methodology/approach – Research papers, publications and websites of well-known apparel companies using FC are reviewed to explore the latest technological advancements in apparel FC. Findings – Given the advances in body measurement, pattern and fit assessment technologies, FC represents a sustainable production approach for the apparel industry. Originality/value – This review examines the state of the field, looks at possible trends in the study and highlights future directions. Keywords Fit customization, Body measurement, 3D patten-making, Virtual fitting, Sizing system Paper type Literature review